PERTANGGUNGJAWABAN HUKUM ANGGOTA KEPOLISIAN REPUBLIK INDONESIA PELAKU TINDAK PIDANA NARKOTIKA ANTARA RANAH PIDANA DAN ETIK - Cahyo Aribowo; Markoni; I Made Kantikha; Joko Widarto; Tuti Elawati (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study is motivated by the existence of dual mechanisms of accountability for members of the Indonesian National Police (Polri) who commit narcotics-related crimes, namely criminal proceedings in the general courts and ethical-administrative proceedings through the Police Professional Code of Ethics Commission (KKEPP). This dual system often raises debates regarding the legitimacy of ethical sanctions, the application of the ne bis in idem principle, and the consistency of law and ethics enforcement within the Indonesian legal system. The purpose of this research is to analyze the legal accountability system for Polri members who commit narcotics crimes in both the criminal and ethical domains, as well as to examine the principles of professional ethics in relation to criminal court decisions and KKEPP decisions. This research applies the legal system theory and professional ethics theory. The method used is normative legal research with statutory, conceptual, and case approaches. The results show that the Indonesian legal system recognizes criminal and ethical accountability as two distinct but complementary mechanisms. Criminal court decisions determine the legal guilt of the offender, while KKEPP decisions assess integrity, moral responsibility, and the professional suitability of Polri members. Ethical sanctions in the form of Dishonorable Discharge (PTDH) do not violate the ne bis in idem principle because they fall within the domain of administrative law and professional ethics. The relationship between criminal and ethical decisions is complementary and plays an important role in maintaining professional integrity, institutional professionalism, and public trust in Polri